Composite Index of Anthropometric Failure (CIAF) among Sonowal Kachari tribal preschool children of flood effected region of Assam, India - Bharali Nitamoni; Singh Kh. Narendra; Mondal Nitish (Anthropological Review, 2019)
Undernutrition is considered to be a serious public health problem in most of the developing countries. Globally, the anthropometric measures are widely used to estimate the magnitude of undernutrition in children. The Composite Index of Anthropometric Failure (CIAF) provides the overall magnitude of undernutrition as an aggregate single measure over the conventional anthropometric indices and helps in identification of single or double or multiple anthropometric failures in preschool children. The present investigation assesses the age-sex specific prevalence of undernutrition using both conventional anthropometric measures and CIAF among Sonowal Kachari tribal preschool children of Assam, India. This cross-sectional investigation was carried out among 362 (162 boys and 190 girls) Sonowal Kachari tribal children younger than 5 years of flood affected regions of Lakhimpur district of Assam, India. Anthropometric measurements of height and weight were measured using standard procedures. Age-sex specific Z-score value of weight-for-age, height-for-age and weight-for-height were calculated by using WHO-Anthro, v. 3.2.2. A child Z-score <−2.00 of any anthropometric indices was considered to be undernourished and the standard CIAF classification was used to calculate the prevalence of undernutrition. The overall prevalence of wasting, underweight, stunting and CIAF was observed to be 11.6%, 22.9%, 36.2%, and 48.6%, respectively. The sex-specific prevalence of wasting (15.8% vs. 6.9%), underweight (30.5% vs. 14.5%) and stunting (42.1% vs. 29.6%) observed to be significantly higher among girls than boys (p<0.05). The girls (61.05%) were found to be more affected than boys (34.9%) by CIAF (p<0.01). The present investigation reported higher magnitude of undernutrition using CIAF over conventional anthropometric measures, hence the CIAF is relatively better indicator that reflects higher magnitude of undernourishment as compared to any conventional anthropometric indices in children. This research investigation has also reinforced the importance of appropriate intervention programme and strategies needed to reduce the prevalence of undernutrition in childhood and in population as a whole.